C-reactive Protein, Genetic Susceptibility, and the Long-Term Risk of Venous Thromboembolism in Patients with Past Cancer - Guan, Yunlong; Gan, Zeyu; Li, Si; Cao, Xi; Zeng, Ao; Li, Jing; Gong, Wei; Deng, Jun; Hao, Xingjie (Thrombosis and Haemostasis, 2024)
Several studies have indicated that C-reactive protein (CRP) level is associated with the risk of venous thromboembolism (VTE) in the general population. However, CRP appears to be unrelated to VTE events in patients newly diagnosed with cancer. As the survival time of cancer patients increases, the effect of CRP on the long-term risk of VTE may change. We aimed to investigate the association between CRP and VTE in cancer survivors and further assess the modification effect of genetic susceptibility.The Cox proportional hazards model was used to evaluate the association between CRP levels and VTE risk as well as to investigate the joint effect of CRP and genetic susceptibility. The Kaplan-Meier curve and restricted cubic spline were used to visualize the relationship between CRP and VTE.This study included 27,806 participants with cancer diagnosis at baseline in the UK Biobank. Over a follow-up period of 344,636 person-years, a total of 1,151 VTE events were recorded. Participants were divided into four groups based on CRP level quartiles. The adjusted hazard ratios (95% CIs) of Q1, Q2, Q3, and Q4 were 1.00, 1.20 (0.99–1.44), 1.25 (1.04–1.50), and 1.51 (1.25–1.82), respectively. For those with high genetic risk of VTE, high CRP had an additional increased risk for VTE.CRP can be used as a predictive biomarker for VTE risk in cancer survivors, especially in those with high genetic risk. Future research can explore whether prevention and treatment strategies for VTE can be developed based on CRP for cancer survivors.
Keywords: venous thromboembolism; C-reactive protein; cancer; polygenic risk score; cohort study